2020
DOI: 10.3390/ma13071700
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Leakage of Endodontic Temporary Restorative Materials around Access Cavities Prepared with Pre-Endodontic Composite Build-Up: An In Vitro Study

Abstract: This study aimed to examine the marginal seal between various commercial temporary restorative materials and exposed dentin/built-up composite. Sixty bovine incisors were cut above the cemento-enamel junction, and half of the dentin was removed to form a step, which was built up using flowable resin composite. The root canals were irrigated, filled with calcium hydroxide, and sealed using one of six temporary sealing materials (hydraulic temporary restorative material, temporary stopping material, zinc oxide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The presented results on dye penetration and particularly the analysis of the T-points comply with a previous in vitro study investigating the marginal integrity between endodontic temporary restorative materials and composite build-ups or bovine dentine (Kameyama et al, 2020). In the present study, the T-point analysis revealed penetration mainly between cervical dentine and preendodontic composite restorations and not between preendodontic composite class-II-restorations and postendodontic composite class-I-restorations when a self-etch adhesive was used.…”
Section: Discussionsupporting
confidence: 90%
“…The presented results on dye penetration and particularly the analysis of the T-points comply with a previous in vitro study investigating the marginal integrity between endodontic temporary restorative materials and composite build-ups or bovine dentine (Kameyama et al, 2020). In the present study, the T-point analysis revealed penetration mainly between cervical dentine and preendodontic composite restorations and not between preendodontic composite class-II-restorations and postendodontic composite class-I-restorations when a self-etch adhesive was used.…”
Section: Discussionsupporting
confidence: 90%
“…An excellent temporary restorative material must prevent the root canal system from being contaminated by saliva, fluids and microorganisms 16 . The composite resin and glass ionomer cement adhere to the tooth structure, preventing the infiltration of oral fluids at the cement-tooth interface 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, a associação do óxido de zinco ao sulfato de cálcio gera um aumento do selamento da interface no dente que foi utilizado o material restaurador. Isso acontece devido o sulfato de cálcio absorver água e como resultado aumentar seu volume PIEPER et al, 2009;KAMEYAMA et al, 2020).…”
Section: Restauradores a Base De óXido De Zinco E Eugenolunclassified
“…Brazilian Journal of Health Review, Curitiba, v. 6, n. 6, p. 28390-28402, nov./dec., 2023 Após a realização do tratamento endodôntico, ou até mesmo quando não é possível realizar em sessão única, uma restauração temporária é necessária a fim de evitar a recontaminação do sistema de canais radiculares. Esse selamento temporário é de grande importância para manter esse sistema livre de infiltração marginal após obturado, e quando sob ação da medicação intracanal, os condutos continuem ainda em controle de sanificação (KAMEYAMA et al, 2020). Essa restauração temporária visa a manutenção da limpeza do canal radicular atuando como barreira física, impedindo a passagem de microrganismos para o interior dos condutos (JESUS E FERNANDES, 2022).…”
unclassified